Hubungan pengetahuan dengan motivasi mencegah komplikasi pada penderita diabetes melitus - Andoko Andoko; Dimas Ning Pangesti; Nurhayati Nurhayati (Program Studi Ilmu Keperawata Fakultas Ilmu Kesehatan Universitas Malahayati, 2020)
Knowledge and motivation in management of diabetes mellitus complicatingBackground: The increasing of diabetes mellitus prevalence and complication occurrence. The number of diabetes mellitus in 2018, there were 654 patients. A pre-survey in January 2019 on 15 respondents, 50.7% patients had a poor knowledge and 54.9% had a poor motivation to prevent complication of diabetes mellitus. Purpose: To know the correlation between knowledge and motivation in management of diabetes mellitus complicatingMethod: A quantitative with cross sectional method. The population was all outpatient at Internal Polyclinic of Bhayangkara Polda Lampung Hospital and the samples were 48 patients. The instruments were questionnaires. The data analsysi by chi square.Results: Shows that 30 respondents (62.5%) had good a knowledge. The other 27 respondents (56.3%) had high motivation in management of diabetes mellitus complicating. There was correlation between knowledge and motivation in management of diabetes mellitus complicating (p value 0.029, OR 4.7).Conclusion: There was correlation between knowledge and motivation in management of diabetes mellitus complicating.The health practitioners should intensify the health promotion to patient by displaying posters and distributing leaflet for hospital visitors to improve their knowledge.Keywords: Knowledge; Motivation; Management; Diabetes mellitus; Complicating Pendahuluan: Adanya peningkatan prevalensi penderita DM, serta meningkatnya angka kejadian komplikasi penderita DM di RS Bhayangkara Polda Lampung tahun 2018 berjumlah 654 penderita. Dari presurvei bulan januari 2019 didapat 15 responden, tingkat pengetahuan kurang sekitar (50,7%) dan yang mempunyai motivasi rendah (54,9%).Tujuan: Untuk mengetahui hubungan antara pengetahuan dan motivasi penderita diabetes melitus.Metode: Penelitian kuantitatif, dan menggunakan cross sectional study, populasipasien yang menderita diabetes melitus di Poliklinik Penyakit Dalam RS Bhayangkara Polda Lampung. Sampelnya sebanyak 48 orang, instrumen menggunakan kuesioner dan analisa data menggunakan uji chi square.Hasil: Tingkat pengetahuan baik 30 responden (62.5%), motivasi tinggi 27 responden (56.3%).Ada hubungan antara pengetahuan dengan motivasi penderita DM dalam mencegah komplikasi ( p value 0,029. OR 4,7).Simpulan: Ada hubungan antara pengetahuan dengan motivasi penderita DM dalam mencegah komplikasi. Saran kepada RS Bhayangkara meningkatkan kegiatan promosi kesehatan tentang pola hidup yang baik bagi klien DM, dengan memasang poster dan membagian leaflet.